Genetic Improvement of Araucaria cunninghamii for Enhanced Industrial Pulp Production - Pamungkas, Bayu; Setiadi, Dedi; Baskorowati, Liliana; Mashudi; Pudjiono, Sugeng; Nurtjahjaningsih, Ida Luh Gede; Susanto, Mudji; Hendrati, Rina Laksmi; Sumardi; Fauzan, Yusuf Sigit Ahmad; Wirabuana, Pandu Yudha Adi Putera (Jurnal Sylva Lestari, 2025)
Araucaria cunninghamii has significant potential as a long-fiber pulpwood source in Indonesia; however, its utilization remains limited due to its dependence on imported raw materials. This study presents the results of a first-generation progeny trial designed to evaluate genetic variation and identify superior genotypes for future breeding programs. This study was conducted in Bondowoso, East Java; the experimental was included 80 families from six provenances (Fakfak, Jayapura, Serui, Wamena, Manokwari, and Queensland) and designed by a Randomized Complete Block Design (RCBD); comprised of 6 provenances, 80 families, 4 blocks, 4 trees per plot with a spacing of 4 m ´ 2 m. After six years, the survival rates ranged from 98.30% to 99.61%, indicating a strong potential for adaptability. Significant differences were observed among families for height, diameter, and volume growth traits. Heritability estimates for height, diameter, and volume at the individual level were 0.30, 0.25, and 0.27, respectively, and 0.48, 0.45, and 0.47 at the family level. Strong genetic correlations were found between height and diameter (r = 0.99), suggesting the potential for indirect selection through breeding. These findings highlight the genetic potential of A. cunninghamii for sustainable pulp production and inform future breeding strategies that focus on growth, adaptability, and wood quality. Keywords: Araucaria cunninghamii, genetic variation, progeny test, pulpwood, heritability, provenance trial